Product and environmental social performance: Varying effect on firm performance - Jayachandran, Satish; Kalaignanam, Kartik; Eilert, Meike (Strategic Management Journal, 2013)
Corporate social performance ( CSP ) consists of actions in different domains that vary in the information they provide stakeholders, and hence, in their effect on firm performance. To demonstrate this, the authors examine the impact of CSP on firm performance in two areas—the product and the environment, referred to as product social performance ( PSP ) and environmental social performance ( ESP ), respectively. PSP has a stronger positive impact on firm performance compared to ESP . The findings using disaggregated measures of PSP and ESP indicate negativity bias in that PSP weakness has a stronger negative impact on firm performance compared to PSP strength . Copyright © 2013 John Wiley & Sons, Ltd.